Distribusi Pandanus Di Pulau Wangi-wangi Kabupaten Wakatobi Sulawesi Tenggara - Medi Hendra; Linda Oktavianingsih; Husdiati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Pandanus is a plant that has two houses (dioecious) that have morphological like shrubs or trees and is difficult to find shelter in another tree, prop roots, and single leaves that mostly have spines along the edges and the base of the leaf. The purpose of this research is to determine the distribution of the Pandanaceae family on Wangi-wangi Island, Wakatobi Regency. The method used field observation technique and data collection done by exploring the Wangi-wangi Island, Wakatobi Regency area. The result of the research is two distribution patterns of Pandanus on Wangi-wangi Island is spread throughout the island for the type of Pandanus tectorius Soland. and Pandanus amaryllifolius Roxb. while the other two species, Pandanus tectorius var. variegatus Back. and Pandanus dubious Spreng. found only on the west side only.